THE INFLUENCE OF PEOPLE, SERVICE AND FACILITIES ON CUSTOMER SATISFACTION AT PT.ANGKASA PURA I (PERSERO) JUANDA INTERNATIONAL AIRPORT SURABAYA - Angda Nublah Mesfautri (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study is to analyze the partially affect of variables People, Service and Facilities on  Customer Satisfaction at PT. Angkasa Pura I (Persero) of  Juanda Airport in Surabaya and to examine the variables, which dominantly affects on Customer Satisfaction at PT. Angkasa Pura I (Persero) of Juanda Airport in Surabaya. The population in this study is employees of 13 Airlines that use facilities of PT. Angkasa Pura I (Persero) – Juanda International Airport Surabaya, with collecting data by questionnaire. The sampling technique was purposive sampling with 56 respondents.   The technique of hypothesis testing use in this study is Multiple Regression Analysis. Result showed that People, Service and Facilities have significantly effects on Customer Satisfaction. In addition. people have dominant effect on Customer Satisfaction at PT. Angkasa Pura I (Persero) – Juanda International Airport in Surabaya.  Keywords: People, Service, Facilities and Customer Satisfaction